IMPACT OF FINANCIAL CYCLES ON BANKING AND LENDING IN EASTERN NORTH CAROLINA - Datskevych, Elizabeth Anastasia (My University, 2025)
The purpose of this research is to examine how financial cycles influence banking and lending in Eastern North Carolina (ENC). This study aims to identify the underlying factors contributing to the disproportionate economic impacts experienced in the region. ENCs suffer more severe consequences during financial downturns and experience less pronounced benefits during upturns due to the region’s predominantly rural composition, persistent economic disadvantages, and limited access to banking infrastructure.
Keywords: Financial cycles; Rural banking access; Socioeconomic disparities